La fabrique du genre dans la presse mexicaine - Nathalie Ludec (Nuevo mundo - Mundos Nuevos, 2014)
The beginning of the feminist movement and its development in Mexico during the 1970s was nourished by European and American influences while searching for its own basis in local reality.Intellectuals, feminists and militants, while recalling past women's struggles, tried to spread the new ideas of this second wave of feminism in the pages of the major periodicals of the moment (Novedades, El Universal, Unomásuno) against all odds. They built feminist history aiming at a readership that was not convinced by their ideas, all the while taking an impartial look at Mexican society. Along other lines, these journalists began, ahead of their time, a task of model and category deconstruction using gender theory. This would be developed later by Joan Scott and, in Mexico and Latin America, by Marta Lamas and Teresita Barbieri. This analysis seeks to underscore the trans-nationalization of issues in a local and global exchange with its roots in Mexican society.